2018
DOI: 10.26480/ecr.01.2018.30.35
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Irrigation, Its Impact on Environment and Health Risk Assessment in Peri Urban Areas of Punjab Pakistan – A Review

Abstract: Due to water scarcity issues in developing countries, wastewater irrigation has become a viable common practice in majority of the agricultural areas of Pakistan. It has been widely claimed that the use of wastewater for irrigation purpose not only helps in addressing the issues of water scarcity but fulfills the nutritional requirements for the cultivation as well. But the municipal wastewater in urban and peri urban areas of Punjab are carrying excessive pollution loads of untreated industrial wastewater, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Different studies have addressed this issue in various cities of Pakistan i.e. in Lahore, Faisalabad, Attock ( Rashid et al., 2018 ), Sargodha ( Ahmad et al., 2019 ), in Karachi ( Shehnaz et al., 2019 ; Aziz et al., 2021 ) and Sawabi ( Ali et al., 2021 ). On the other, studies have revealed that only 2% of cities are availing wastewater treatment systems in Pakistan, whilst 80% of the cities use untreated discharge for irrigation purposes ( Ullah et al., 2018 ; Shahid et al., 2020 ; Bashir et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have addressed this issue in various cities of Pakistan i.e. in Lahore, Faisalabad, Attock ( Rashid et al., 2018 ), Sargodha ( Ahmad et al., 2019 ), in Karachi ( Shehnaz et al., 2019 ; Aziz et al., 2021 ) and Sawabi ( Ali et al., 2021 ). On the other, studies have revealed that only 2% of cities are availing wastewater treatment systems in Pakistan, whilst 80% of the cities use untreated discharge for irrigation purposes ( Ullah et al., 2018 ; Shahid et al., 2020 ; Bashir et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%